PEMAHAMAN DAN HARMONISASI KONSEP-KONSEP STANDAR PELAYANAN MINIMAL DESA TERHADAP APARATUR DESA ADINUSO KECAMATAN REBAN KABUPATEN BATANG - Endro Tri Susdarwono; M. Syamsul Rizal (Universitas Halu Oleo, 2020)
This study aims to provide a description of the understanding and harmonization of the concepts of village minimum service standards according to the Republic of Indonesia's Minister of Home Affairs Regulation Number 2 of 2017 to the apparatus of the Adinuso Village, Reban District, Batang Regency. This research is based on community service in Adinuso Village, Reban District, Batang Regency from January to February 2020. In this study, the approach used is a combination of qualitative and quantitative. A qualitative approach is used to describe how the process provides understanding and harmonization of the concepts of village minimum service standards according to the Republic of Indonesia's Minister of Home Affairs Regulation Number 2 of 2017 to the Adinuso Village apparatus, Reban District, Batang Regency, while the quantitative approach used is hypothesis testing of the signs used to analyze service standards village before and after community service is carried out. Meanwhile, in order to ascertain whether or not there is a change in the state of public service standards, before and after treatment (before and after treatment research design) a hypothesis testing method is used for changes using the Mac Nemar change test. The conclusions of this study are (1) that the community service carried out can improve the service standards of the Village Government community, (2) that there has been a change in the standard state of community service in the Adinuso Village Government, Reban District, Batang Regency after community service.